Editorial - Miranda, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The Colombian Society of Horticultural Sciences (SCCH) and the Universidad Pedagógica y Tecnológica de Colombia (UPTC) as editors of the Colombian Journal of Horticultural Sciences wish to extend our special greetings to our authors and readers in these moments when the world is undergoing a difficulty of great proportions, which has been affecting the work of the world community and neither science nor technology has been able to remain outside the effects of the well-known COVID19 pandemic. However, with all the difficulties, the horticultural scientists in the world continue to work and show their results in the generation of new knowledge, as a contribution to the solution of the agricultural food problem in different countries.